Person Deixis in some Letters Written by Rosalía de Castro and Emilia Pardo Bazán Studied from the Functional Discourse Grammar - Fernández Martín, Patricia (Madrygal. Revista de Estudios Gallegos, 2019)
The aim of this paper is to compare the person deixis of the letters written by Rosalía de Castro to Manuel Murguía, on the one hand, with the ones written by Emilia Pardo Bazán addressed to Benito Pérez Galdós, on the other. For this, the Functional Discourse Grammar (FDG) is used to analyze the personal deixis which refers to the interlocutors in the epistolar communication, taking as a starting point the concept of exophoric reference. Thus, in the first part, the theoretical framework is exposed: the history of the chosen linguistic corpus; the main factors of FDG and the description of the linguistic phenomena to be analyzed –person deictics which appear in the signatures, in the directions and in the body of the text, if they allude to the interlocutors of the epistolary exchange. In the second part, the analysis is offered at the interpersonal level, at the representational level and at the morphosyntactic level, according to the FDG's primary parameters. The main conclusion highlights that the relationship De Castro-Murguía denotes a deep affection and a wide confidence that, with constant fluctuations, becomes loving passion and friendship in the relationship Pardo Bazán-Pérez Galdós.
Keywords: Personal Deixis; Epistolar Genre; Rosalía de Castro; Emilia Pardo Bazán